Workshop on Parental Involvement for Children Learning - Somariah Fitriani; Yessy Yanita Sari (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Technology like the Google Meeting platform, Zoom Meeting, Google Classroom, Webex, and other apps were extensively used for online learning. These platforms or programs are still utilized today, even after the pandemic, and they significantly aid in the learning process. Due to the requirement for knowledge and skills in using these programs and platforms, this condition presents additional challenges for children in kindergarten and elementary school. As a result, parents are crucial to their children's academic performance. This community service has as its goal educating and informing parents about the value of being involved in their children's educational journey. 23 parents attended this service activity, which was carried out in the form of a workshop. The implementation method is carried out by interactive lecture methods, brainstorming, sharing experiences with students' parents and discussions. The results of the online survey revealed the participants' satisfaction with this activity which provided enlightenment and knowledge to them.